Determinants influence in intention to purchase healthy food among consumer in Melaka / Vaneitta Agiu - Agiu, Vaneitta (Faculty of Business and Management, 2020)
This study is aim to identify the determinants that influence the intention to purchase healthy food among consumer in Melaka. This study is important to know what other determinants that can influence the consumer intention to purchase healthy food besides when the consumer are already aware the important of nutrition in their daily food intake. Thus, this study will elaborate more about the determinants that can influence the intention to purchase healthy food and can help consumer gained new information from this study. The information for this study will gathered using the primary which is collect data through the questionnaire and secondary data which is from the online journals, methodology textbook or articles. Meanwhile the convenient sampling was used to collect data from 384 respondents. The objective for this study is to determine the relationship between nutrition, cost-saving, safety, convenience, knowledge and intention to purchase healthy food, to study the most dominant determinants influencing healthy food purchase and to suggest for health agency or body on healthy food intake campaign. The findings of this study will be measures using the Statistical Package for Social Science (SPSS) with the frequency analysis, descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis.